Overview of central banks' in-house credit assessment systems in the euro area - Laura Auria; Markus Bingmer; Carlos Mateo Caicedo Graciano; Clémence Charavel; Sergio Gavilá; Alessandra Iannamorelli; Aviram Levy; Alfredo Vignolo Maldonado; Florian Resch; Anna Maria Rossi; Stephan Sauer (European Central Bank (ECB), 2021)
The in-house credit assessment systems (ICASs) developed by euro area national central banks (NCBs) are an important source of credit risk assessment within the Eurosystem collateral framework. They allow counterparties to mobilise as collateral the loans (credit claims) granted to non-financial corporations (NFCs). In this way, ICASs increase the usability of non-marketable credit claims that are normally not accepted as collateral in private market repo transactions, especially for small and medium-sized banks that lend primarily to small and medium-sized enterprises (SMEs). This ultimately leads not only to a widened collateral base and an improved transmission mechanism of monetary policy, but also to a lower reliance on external sources of credit risk assessment such as rating agencies. The importance of ICASs is exemplified by the collateral easing measures adopted in April 2020 in response to the coronavirus (COVID-19) crisis. The measures supported the greater use of credit claim collateral and, indirectly, increased the prevalence of ICASs as a source of collateral assessment. This paper analyses in detail the role of ICASs in the context of the Eurosystem's credit operations, describing the relevant Eurosystem guidelines and requirements in terms of, among other factors, the estimation of default probabilities, the role of statistical models versus expert analysis, input data, validation analysis and performance monitoring. It then presents the main features of each of the ICASs currently accepted by the Eurosystem as credit assessment systems, highlighting similarities and differences.
Keywords: E58; 330; credit assessments; credit risk models; credit claims; ratings; ICAS